Navigating Challenges in the Penta Helix Model: Collaborative Strategies and Obstacles in Countering Extremism in Surabaya, Indonesia - Wibowo, Prihandono; Hapsari, Renitha Dwi; Ascha, Muchammad Chasif; Widjaya, Salsa Febiola Gading; Octavia, Afissa Hanani (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2025)
This study examines the challenges in implementing the Penta helix model to counter radicalism and terrorism in Surabaya, Indonesia. Given Surabaya's strategic importance and vulnerability to extremism, the research seeks to assess how collaboration among government, academia, media, civil society, and the private sector functions within this framework. Employing a descriptive-qualitative approach, data were gathered through semi-structured interviews with key stakeholders, including law enforcement, religious leaders, civil society, and media representatives, supplemented by document analysis. The findings indicate that while the Penta helix strategy has been partially operationalised, several challenges remain. These include minimal involvement of the business sector, fragmented stakeholder coordination, budgetary limitations, and a notable absence of gender mainstreaming despite the involvement of women in previous terrorist acts. These limitations reduce the model’s effectiveness in preventing and countering violent extremism. The study highlights the need to strengthen inter-sectoral collaboration by fully implementing the National Action Plan (RAN PE), institutionalising business sector contributions through CSR, and incorporating gender perspectives into local counter-terrorism policies. This research contributes to the discourse on collaborative governance in extremism prevention by offering a localised analysis of the Penta helix model. Its originality lies in identifying gender mainstreaming and private sector gaps as underexplored barriers, thereby extending existing knowledge on policy implementation at the municipal level.